2010
DOI: 10.1101/gr.111211.110
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals the role of splicing polymorphisms in regulating human gene expression

Abstract: Expression levels of many human genes are under the genetic control of expression quantitative trait loci (eQTLs). Despite technological advances, the precise molecular mechanisms underlying most eQTLs remain elusive. Here, we use deep mRNA sequencing of two CEU individuals to investigate those mechanisms, with particular focus on the role of splicing control loci (sQTLs). We identify a large number of genes that are differentially spliced between the two samples and associate many of those differences with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 51 publications
6
102
1
1
Order By: Relevance
“…To enable a greater number of type 2 diabetes-associated loci to be examined by the more powerful allelic expression approach, future studies may consider using intronic SNPs to measure allelic expression. Allelic expression measurements calculated from intronic SNPs have been shown to be highly correlated with values calculated from linked exonic SNPs (16). While this is, to our knowledge, the first report of a systematic use of allelic expression measurements in human islets to identify likely causal genes at type 2 diabetes GWAS loci, there are other published studies that have reported allelic imbalance in human islets at single loci.…”
Section: Discussionmentioning
confidence: 79%
“…To enable a greater number of type 2 diabetes-associated loci to be examined by the more powerful allelic expression approach, future studies may consider using intronic SNPs to measure allelic expression. Allelic expression measurements calculated from intronic SNPs have been shown to be highly correlated with values calculated from linked exonic SNPs (16). While this is, to our knowledge, the first report of a systematic use of allelic expression measurements in human islets to identify likely causal genes at type 2 diabetes GWAS loci, there are other published studies that have reported allelic imbalance in human islets at single loci.…”
Section: Discussionmentioning
confidence: 79%
“…It is well known that there are many molecular mechanisms that allow different genotypes to influence gene expression. These include allele-specific expression through the modulation of activity of cis-regulatory elements, the regulation of transcript isoform levels through disruption of the splicing machinery, and the modification of chromatin accessibility and transcription factor binding Pickrell et al 2010;Lalonde et al 2011;Degner et al 2012). However, the mechanisms underlying the interaction between these expression-controlling genotypes are poorly understood.…”
Section: Formation Of Evqtlmentioning
confidence: 99%
“…Despite these observations, which point to the functional importance of exon usage regulation, there is also conflicting evidence: Splicing factor recognition motifs are short and degenerate, exon usage can vary between individuals because of subtle genetic variations in cis-regulatory regions (15,16), and it has been suggested that a stochastic model of processes in the splicing machinery explains most splicing variation (17). In fact, a comparative analysis of transcriptomes associated with multiple human individuals found a high prevalence for noisy, presumably erroneous, splicing, particularly in low-abundance isoforms (18).…”
mentioning
confidence: 99%